Effect of Foliar Methionine Application on the Biochemical Characteristics of Turnip (Brassica rapa L. subsp. rapa) and Red Beet (Beta vulgaris L.) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2026)
This study aims to evaluate the effect of foliar application of the amino acid methionine on the biochemical traits of turnip (Brassica rapa L. subsp. rapa) and red beet (Beta vulgaris L.). A field experiment was conducted using a completely randomized design with four methionine concentrations (control, 0.5%, 1%, and 1.5%) and eight replicates. The results showed that the effects of methionine spraying on biochemical traits varied depending on its concentration, with the highest increase in chlorophyll content recorded at 1.5%. Lower concentrations enhanced the soluble sugar content in leaves and roots, whereas higher concentrations caused a reduction. Methionine had a stimulatory effect on soluble protein content in leaves but an inhibitory effect in roots, reflecting a differential physiological response between plant organs. The total free amino acid content exhibited concentration-dependent responses. Proline content decreased in turnip, indicating a role of methionine in improving the physiological status of the plant, while in beet, low concentrations maintained the same proline level as the control, but it slightly increased at higher concentrations. We conclude that methionine contributed to the improvement of certain biochemical traits at lower concentrations, while its effects were mostly negative at higher concentrations.
Keywords: Turnip (Brassica rapa); Red beet (Beta vulgaris); Biochemistry